The effects of Experiential values and satisfaction on revisit intention - Murtini, Sri (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2021)
The purpose of this study was first to examine how goal-oriented attendees and experiential-oriented attendees were related to their overall satisfaction and loyalty of the destination with respect to Gedong Songo Temple in Semarang Central Java. It also investigated how these relations are mediated by the different dimensions of experiential consumption values such as consumer return on investment (CROI, active value), escapism (active value) and service excellence (reactive value), and aesthetics (reactive value). Self-administered questionnaires were distributed to and collected from 266 sampling respondents as subjects consisting of local and international tourists and indicating a response rate of about 88 percent. Total 13 hypotheses were tested using structural equation model (SEM) with AMOS, and the results were interpreted adapting Mathwick’s (2001) typology of experiential value. The managers at Gedong Songo temple should understand what drives the tourists/attendees. Implementing experiential marketing through various dimensions of experiential value can attract more potential attendees, provide unique experiences and create favorable perceptions toward the destination. The research is original in terms of conceptualizing and empirically testing the relation between experiential values and behavior loyalty within the special events and festivals with a specific focus on international temple festivals. A finding of particular importance here is verifying the unique characteristics of goal-/experiential-oriented attendees in festival settings and determining the linkages between these different attendees and active/reactive experiential values, not to mention the relation with the overall satisfaction and loyalty to the festival destination.